Land use change science, policy, and management - Aspinall, Richard, 1956-; Hill, Michael J. 1937- (CRC Press, 2008)
Presents spatial theories and methodologies that support an integrated approach to analysis of land use change. Focusing on spatial representation and modeling, this book addresses such important scientific issues as the dynamics of change, integration and feedback between system elements, and scale issues in space and time.
Keywords: Land use -- Environmental aspects.; Land use -- Management.; Land use -- Case studies.; Bonn.; elektronické knihy; electronic books